(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Fruit and vegetable products are one of the main items of agricultural export of Uzbekistan. The export potential of the agricultural sector of our country is due to favorable natural and climatic conditions, sufficient labor resources, the presence of a relatively developed infrastructure, and the level of provision with basic production assets.